Synthesis and biological activity of hydrazide-hydrazones and their corresponding 3-acetyl-2,5-disubstituted-2,3-dihydro-1,3,4-oxadiazoles - KAYMAKÇIOĞLU, BEDİA (SPRINGER BIRKHAUSER, 2012)
Various 3-acetyl-2,5-disubstituted-2,3-dihydro-1,3,4-oxadiazoles (11-20) were prepared by the reaction of aryl substituted hydrazones of 4-fluorobenzoic acid hydrazide (1-10) with acetic anhydride. The structures of the synthesized compounds 11-20, were confirmed by UV, IR, H-1-NMR and mass spectroscopic methods. Antifungal evaluation of the hydrazide-hydrazones 1-10 and corresponding 3-acetyl-2,5-disubstituted-2,3-dihydro-1,3,4-oxadiazoles 11-20, against clinical and standard Candida pathogens have been performed by using agar diffusion to indentify the active compounds, which were later subjected to a broth microdilution assay to justify the activity level in terms of minimum inhibitory concentrations (MIC). 4-Fluorobenzoic acid [(5-bromothiophen-2-yl)methylene]hydrazide, showed the highest inhibitory activity against Candida albicans (MIC: 125 mu g/ml), and when compared with ketoconazole. In addition, bioauthographic antifungal activity against plant pathogenic fungi such as Colletotrichum, Botrytis, Fusarium, and Phomopsis was conducted. 4-Fluorobenzoic acid [(5-bromothiophen-2-yl)methylene]hydrazide was the most active analog against P. viticola with 91% inhibition at 30 mu M after 144 h. Furthermore, known and the newly synthesized compounds were also screened through a panel of bioassays to determine their anti-inflammatory, cytotoxic, and antioxidant activities in mammalian cells. 3-Acetyl-5-(4-fluorophenyl)-2-(3-hydroxy-4-methoxyphenyl)-2,3-dihydro-1,3,4-oxadiazole, showed a strong inhibition of NF-kappa B-dependent transcription in SW1353 cells with IC50 value of 0.75 mu g/ml. 4-Fluorobenzoic acid [(3-hydroxy-4-methoxyphenyl)methylene]hydrazide, and 3-acetyl-5-(4-fluorophenyl)-2-(3-hydroxy-4-methoxyphenyl)-2,3-dihydro-1,3,4-oxadiazole on intracellular ROS generation in PMA induced HL-60 cells demonstrated potent activity with IC50 values of 0.9 mu g/ml. A strong inhibition of the activity of iNOS activity in LPS induced RAW 264.7 cells was observed for 3-acetyl-5-(4-fluorophenyl)-2-(4-hydroxyphenyl)-2,3-dihydro-1,3,4-oxadiazole with IC50 value of 0.3 mu g/ml.
Keywords: Hydrazide-hydrazones; 1,3,4-Oxadiazoles; Anti-inflammatory; Cytotoxicity; Antioxidant; Antifungal; ANTIMICROBIAL ACTIVITY